A “Not Particularly Felicitous” Phrase: A History of the “Behavioral Sciences” Label - Pooley, Jefferson D. (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
The article reconstructs the history of the "behavioral sciences" label, from scattered interwar use through to the decisive embrace of the newly prominent Ford Foundation in the early Cold War. The rapid uptake of the label, the article concludes, was the result of the Ford Foundation’s 1951 decision to name its social science unit the “Behavioral Sciences Program” (BSP). With Ford’s encouragement, the term was widely adopted by quantitative social scientists eager to tap the foundation’s social science funds. The label’s newness and its link to the gigantic foundation’s initiative generated much suspicion and resistance as well.